2021
DOI: 10.1016/j.jinf.2020.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Older age is associated with sustained detection of SARS-CoV-2 in nasopharyngeal swab samples

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…There is also limited data on the time taken for SARS-CoV-2 clearance in infected patients and the factors that influence this duration. Hattori et al [8] reported that an older age is associated with a longer duration of SARS-CoV-2 RNA detection; however, this report lacked multivariate analysis and an evaluation of the differences based on age. Thus, little is known about the factors that influence the positive duration.…”
Section: Discussionmentioning
confidence: 88%
“…There is also limited data on the time taken for SARS-CoV-2 clearance in infected patients and the factors that influence this duration. Hattori et al [8] reported that an older age is associated with a longer duration of SARS-CoV-2 RNA detection; however, this report lacked multivariate analysis and an evaluation of the differences based on age. Thus, little is known about the factors that influence the positive duration.…”
Section: Discussionmentioning
confidence: 88%
“…Sensitivity of ICA markedly decreased over time after symptom onset, particularly in saliva. It is well documented that SARS-CoV-2 tends to persist longer in NPS than in saliva[12, 13]. It is thus reasonable to speculate that lower sensitivity of saliva ICA is due to late sampling rather than the difference in antigen load between saliva and NPS.…”
Section: Discussionmentioning
confidence: 98%
“…We excluded COVID-19 patients who showed a significant level of recovery and those who had severe complications. Some of the PCR test data from the patients with COVID-19 included in this manuscript have been presented in our previous papers [19][20][21].…”
Section: Patientsmentioning
confidence: 99%